Adsorption Characteristics of Cu(II) and Pb(II) Ions onto Natural Manganese Ore from Aqueous Solution - Taihong Shi; Shiguo Jia; Ying Chen; Yinghong Wen; Changming Du; Zhuochao Wang; Rongling Qiu (Adsorption Science & Technology)
The adsorption of heavy metal cations, i.e. Pb(II) and Cu(II), from aqueous solution by a natural manganese mineral (rhodochrosite) was investigated. The properties of the ore were studied using SEM, FT-IR, XRD and BET methods. The value of pH pzc was determined using an equilibrium technique to give a value of 7.8 ± 0.1 which was not affected by the presence of added electrolyte. Batch experiments were carried out to investigate the adsorption processes. Kinetic experiments indicated that the processes could be simulated by a pseudo-second-order model and the Elovich equation, suggesting that the process may be chemisorption in nature. The adsorption capacity increased with increasing initial concentration of metal cations. The resulting isotherms could be described by the Langmuir relationship, with the adsorbent showing a higher affinity towards Pb(II) ions than Cu(II) ions. Thermodynamic analysis indicated that the adsorption process was endothermic and possibly chemical in nature with positive values of ΔH 0 . Positive ΔS 0 values suggested that a dissociative process was involved. The small positive ΔG 0 values indicated that the adsorption processes required a small amount of energy. The adsorption processes were only slightly influenced by the concentration of added electrolyte but were strongly dependent on the pH value. It is proposed that the most possible mechanism for the adsorption processes involves inner-sphere complexation.